Ocular Manifestations in Neuroendocrine Tumors: A Review Article - Aleksandra Hrapkowicz; Joanna Szydziak; Kinga Janowska; Martyna Wrześniewska; Julia Wołoszczak; Hanna Zając-Pytrus (Kazimierz Wielki University, 2024)
Introduction: Neuroendocrine tumors (NETs) are a diverse group of tumors that arise from neuroendocrine cells and can synthesize and secrete neuropeptides or hormones. Although NETs usually originate from the gastrointestinal tract or bronchopulmonary tree, they can affect various organs, including the eye. The majority of ocular association with neuroendocrine tumors results from metastasis that affects the orbit, however, primary ocular tumors have been reported. Purpose of the study: The article reviews the presentation of ocular manifestations in neuroendocrine tumors including pheochromocytoma, ocular paraganglioma, gastrointestinal and bronchial NETs, Merkel cell carcinoma and neuroendocrine metastasis. Materials and methods:  In order to summarize the current knowledge on the topic, a literature review of English language papers with a focus on the most current literature was performed. The review was conducted with the PubMed database with 43 works used, accessed before September 2024. Conclusions: Instances of neuroendocrine tumors leading to ocular manifestations have become increasingly prevalent. These nonspecific symptoms can make it challenging to diagnose ocular NETs. Ocular manifestations are not typically the primary symptom, but patients with tumors located in the eye may experience symptoms such as eye pain, blepharitis or exophthalmos. Ocular motility and vision may also be affected. It is crucial to study the association between those symptoms and NETs, in order to develop a more comprehensive understanding of the matter.